Surroundings a history of environments and environmentalisms - Benson, Etienne, 1976- (The University of Chicago Press, 2020)
"The English word "environment" dates to the mid-nineteenth century, and the concept that it was invented to describe is not much older. Only since the late eighteenth century, and only in certain contexts, has it become common to believe that life can best be explained in environmental terms. Surroundings is the first full history of the concept - one that shows how it became compelling to particular communities of people. Today we confront the legacies of this long history, which the author argues has made it difficult to speak coherently and persuasively about questions of environmental justice and equity. The history recounted in Surrounded can help us better understand why we find ourselves in this predicament and what we might do about it. For it uncovers not only the diversity of forms that environmentalism has taken in the past but how paying attention them can open our eyes to the promising new varieties of environmentalism that are emerging today"--